Réponses

  • Utilisateur Brainly
2014-08-29T17:33:47+02:00
Développer puis réduire :

(1 + 3x)(7 + 5x)
= 7 + 5x + 21x + 15x²
= 15x² + 26x + 7

(- 6 + x)(3 - x)
= - 18 + 6x + 3x - x²
= - x² + 9x - 18

(x + 3)(2x + 4) - 3(4x - 1)
= 2x² + 4x + 6x + 12 - 12x + 3
= 2x² - 2x + 15
2014-08-29T18:31:28+02:00
Développer puis réduire :

(1 + 3x) (7 + 5x)
= 7 + 5x + 21x + 15x²
= 15x² + 5x + 21x + 7
= 15x² + 26x + 7

(- 6 + x) (3 - x)
= - 18 + 6x + 3x - x²
= - x² + 6x + 3x - 18
= - x² + 9x - 18

(x + 3) (2x + 4) - 3 (4x - 1)
= 2x² + 4x + 6x + 12 - 12x + 3
= 2x² + 4x + 6x - 12x + 12 + 3
= 2x² - 2x + 15